A Dance Movement Psychotherapy Intervention for the Wellbeing of Children With an Autism Spectrum Disorder: A Pilot Intervention Study - Aithal, Supritha; Karkou, Vicky; Makris, Stergios; Karaminis, Themis; Powell, Joanne (Frontiers in Psychology, 2021)
Background: Sustaining the wellbeing for children with an autism spectrum disorder (ASD) can be highly demanding. Dance Movement Psychotherapy (DMP), a form of psychotherapy with a non-verbal character, may present as a relevant intervention option for this group of children. Methods : A protocol-based group DMP intervention was developed and implemented in two special educational needs schools in the North West of England. We aimed to investigate the effects of DMP on children with ASD using the Social Communication Questionnaire (SCQ) and Strengths and Difficulties Questionnaire (SDQ). Twenty-six children aged between 8 to 13 years (mean age = 10.65 years) with ASD were randomly allocated to DMP and a control group with standard care, following a crossover research design. Results : Results showed no significant carryover or period effects for either the SCQ or SDQ (p>0.05). A significant intervention effect was found only for SCQ (p=0.005) but not for SDQ (p>0.05). ANCOVAs were performed on the data before the crossover to test for differences in SCQ and SDQ scores between the DMP intervention and control groups while controlling for pre-intervention scores. Those in the DMP intervention group presented significantly lower SCQ scores following the intervention period than those in the control group (p=0.001). No significant differences in post-intervention SDQ scores were found between DMP intervention and control groups (p=0.2). However, minimal clinically important differences (MCID) were reached for both SCQ and SDQ measures before crossover for those in the DMP intervention group. Moreover, repeated measures ANOVAs performed on SCQ and SDQ measures following crossover were significant, with the change in both SCQ (p=0.001) and SDQ (p=0.009) pre-and post-intervention being significantly greater for those in the DMP intervention than the control group. Conclusions: The pilot DMP intervention has shown promising results on the social and emotional wellbeing of children with ASD irrespective of whether they preferred verbal or non-verbal mode of communication. Limitations and appropriateness of the research methods implemented in this study for their use in a large RCT are discussed in detail. Overall, our findings highlight the value of creative therapies for improving the lives of young vulnerable groups.